Evaluating architectural appeal in Turkish shopping mall investments: Insights from investors and consumers - Yogurtcu, Fatma Bengu; Koksal, Almula (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2025)
In modern society, shopping malls are key elements of daily consumer activity. Even though some studies indicate that spatially architectural appeal is considered as one of the supportive factors on commercial performance and also an attractiveness component to visit mall, it is open to be proven this aspect by comparing from perspective of investors and consumers in T & uuml;rkiye among other influencing factors. To address this gap, surveys were conducted with purposeful sample of institutional investors to ascertain their rankings of investment success factors based on the existing literature and consumers' preference of shopping malls. The data analysis commenced with an assessment of normality, which was followed by measuring importance level of the variables was evaluated using the Friedman test. Mann-Whitney U test was utilized to compare the priority variables for both investors and consumers groups. The findings suggest that decision-makers in T & uuml;rkiye, deemed the presence of anchors, location of the investment, and tenant mix structure more critical than architectural appeal. For consumers, factors such as product/price variety, entertainment opportunities, food and beverage services are primary reasons to frequent a mall. Based on the comparison results, location was considered most important by investors, while consumers found product/price diversity more attractive. This study makes a unique contribution to the literature by offering a comparative analysis of shopping mall investments' performance from the perspectives of entrepreneurs and consumers alike, providing insights for entrepreneurs, developers, designers, and retailers.
Keywords: Architectural appeal; consumers; Friedman; investors; shopping mall; ATTRACTIVENESS; IMAGE; DETERMINANTS; PERFORMANCE; EXPERIENCE; CUSTOMERS; CENTERS; IMPACT; Architecture